Human herpesvirus‐8‐related Kaposi's sarcoma after liver transplantation successfully treated with cidofovir and liposomal daunorubicin - Verucchi, G.; Calza, L.; Trevisani, F.; Zambruni, A.; Tadolini, M.; Giuliani, R.; Manfredi, R.; Andreone, P.; Chiodo, F.; Bernardi, M. (Transplant infectious disease, 2005)
: The iatrogenic form of Kaposi's sarcoma (KS) is typically observed among transplant recipients, and the most appropriate therapeutic approach (usually including reduction of immunosuppression, specific chemotherapy, and/or administration of antiviral agents against human herpes virus‐8) is still controversial. Available experiences on the effect of the anti‐herpes viruses drug cidofovir provide conflicting results. Herein, we report the clinical, histological, and virological features of a liver transplant recipient successfully treated with a combined therapy of cidofovir and liposomal daunorubicin, associated with a reduction of the immunosuppressive regimen, for an advanced cutaneous and visceral KS.